Kontes Makeup: Pemberdayaan Masyarakat Desa Rantih Melalui Seni Tata Rias - Ika Parma Dewi; Agung Ramadhan, Elga Fahreza Fahmi, Trisya Ivana Shallum, Zahwa Devilia, Muhammad Ihsan, Silva Yulfa (CV. ITTC INDONESIA, 2025)
The Community Service Program (KKN) of Universitas Negeri Padang in Desa Rantih in 2024 conducted a Makeup Contest as an effort to empower the community by enhancing makeup skills. The activity aimed to develop participants' creativity, build self-confidence, and strengthen the relationship between KKN students and the local community. The methods used in this activity included training and hands-on practice, where participants were divided into teams consisting of a makeup artist and a model. The results showed high enthusiasm from participants, including mothers, teenagers, and children, as well as a significant improvement in their makeup skills.